The Effect of Problem-Based Learning (PBL) Model through Differentiated Approach in the Merdeka Curriculum on the Learning Achievement of Eleventh Grade Students at SMA Negeri 3 Surakarta - Fitriyanto, Muhammad Firdhaus; Martono , Trisno (The Future of Education Journal, 2024)
This study aims to examine the impact of Problem Based Learning (PBL) via differentiated teaching on the academic performance of eleventh-grade students at SMA Negeri 3 Surakarta. This study employs a Quasi-Experimental research approach. The sampling method included cluster random selection of students from class XI at SMA Negeri 3 Surakarta. The research sample comprises students from class XI F-8 designated as the experimental group and class XI F-9 as the control group. This study use tests and documentation for data collecting. The methodologies for instrument evaluation include validity assessment, reliability assessment, difficulty level analysis, and item discrimination analysis. Data analysis include normality checks, homogeneity tests, and hypothesis testing using independent t-tests performed with SPSS. This study's findings demonstrate that the independent t-test produced a significant value of 0.001. The independent t-test findings indicate the acceptance of H1 and the rejection of H0. Consequently, it can be inferred that the implementation of the Problem Based Learning (PBL) model via a differentiated approach influences the academic performance of eleventh- grade students in economics at SMA Negeri 3 Surakarta.